Фразеологізми та сталі вислови із компонентом червоний: українсько-словацько-польські паралелі - Кузь, Галина (Slavia Orientalis, 2025)
The article presents a comparative analysis of phraseological units and fixed expressions containing the component red in Ukrainian, Slovak, and Polish, from the perspectives of linguoculturology, language pedagogy, and translation studies, within a broad cultural and linguistic context. The selected phraseological material is categorized based on the semantics of the color term red within fixed expressions, thereby constructing the semantic field of this color designation. The comparative analysis reveals a significant number of equivalent units in terms of both meaning and form across the three languages, while also identifying a range of language-specific, non-equivalent phraseological expressions. Particular difficulty for learners of these languages as foreign languages is posed by so-called “false friends” – units that share an identical form but differ partially or completely in meaning. Phraseological expressions and multi-component color terms serve as carriers of unique linguocultural information, reflecting specific cultural realities.